Sounding the Cape : music, identity and politics in South Africa - Martin, Denis (African Minds, 2013)
For several centuries, Cape Town has accommodated a great variety of musical genres which have usually been associated with specific population groups living in and around the city. Musical styles and genres produced in Cape Town have therefore been assigned an identity which is first and foremost social. This volume tries to question the relationship established between musical styles and genres, and social - in this case, pseudo-racial - identities. This book recomposes and examines through the theoretical prism of creolisation the history of music in Cape Town, deploying analytical tools borrowed from studies of identity configurations. The author concludes that, were music given a greater importance in educational and cultural policies, it could contribute to fighting division and promote the notion of a nation that, in spite of the violence of racism and apartheid, has managed to invent a unique common culture.